Trousse d'accompagnement au changement d'échelle - TIESS (2022)
Cette trousse contient de nombreuses ressources pour sensibiliser un porteur ou une porteuse de projet aux stratégies de changement d’échelle (CÉ) et l’accompagner pas à pas dans sa démarche de diversification, d’essaimage, de création de franchise, de coopération ou autre

Changer d'échelle en économie sociale - Planifier l’essor et décupler les retombées de votre entreprise d’économie sociale - TIESS (2017)
En économie sociale, le Québec innove depuis longtemps. Au fil des années, des entreprises d’économie sociale ont développé des modèles qui se sont répandus à travers la province et qui ont même suscité un intérêt à l’étranger. Et cela continue ! Les idées, les communautés mobilisées et les promoteurs de projets engagés continuent d’enrichir le secteur de l’économie sociale. Mais comment augmenter la portée de leur travail ? Comment en faire profiter davantage de gens ? Comment aider les entreprises d’économie sociale à prendre une place encore plus importante, à consolider leurs assises et à avoir une participation accrue à une économie plus démocratique au service des collectivités ?

ISSaQ 4.0: un questionnaire auto-administré sur le potentiel de mise à l'échelle des innovations en santé et en services sociaux - Unité de soutien SSA Québec; Corôa, Roberta D.C.; Ben Charif, Ali; Plourde, Karine V.; Gogovor, Amédé; Légaré, France (Unité soutien SSA Québec, 2023)
ISSaQ 4.0 permet aux équipes d’évaluer le potentiel de mise à l’échelle de leurs innovations. Il s’agit d’un questionnaire auto-administré.

Making a Difference Strategies for Scaling Social Innovation for Greater Impact - FRANCES WESTLEY (2010)
This article explores the strategies and dynamics of scaling up social innovations. Social innovation is a complex process that profoundly changes the basic routines, resource and authority flows, or beliefs of the social system in which it occurs. Various applications of marketing and diffusion theory are helpful to some extent in understanding the trajectories or successful strategies associated with social innovation. It seems unwise, however, to rely solely on a market model to understand the dynamics of scaling social innovation, in view of the complex nature of the supply-demand relation with respect to the social innovation market. Instead, the authors propose a distinctive model of system transformation associated with a small but important group of social innovations and dependent on discontinuous and cross-scale change. This paper focuses on the challenge of scaling up social innovations in general and in particular the dynamics of going to scale

Scaling up social innovation: a meta-synthesis - MORAIS-DA-SILVA, RODRIGO LUIZ; WÜNSCH TAKAHASHI, ADRIANA ROSELI; SEGATTO, ANDREA PAULA (2016)
This paper aims to analyze how features raised in the case studies in the field of social innovation, from the meta-synthesis methodology proposed by Hoon (2013), indicate factors that promote social innovation scalability

Scaling Out, Scaling Up, Scaling Deep: Advancing Systemic Social Innovation and the Learning Processes to Support it - J.W. McConnell Family Foundation; Tamarack Institute; by Darcy Riddell; Michele-Lee Moore (2015)
How can brilliant but isolated experiments aimed at a solving the most pressing and complex social and ecological problems become more widely adopted and lead to transformative impact? Leaders of social change and innovation often struggle to expand their impact on social systems, and funders of such change are increasingly concerned with the scale and positive impact of their investments. In 1998, the Montreal-based J.W. McConnell Family Foundation pursued a deliberate granting strategy known as Applied Dissemination to reframe approaches to replicating successful projects. A few years later, the Foundation began convening its grantees receiving funding from the Applied Dissemination (AD) program to accelerate the impacts of their initiatives, develop a stronger understanding of the complex systems in which they worked, and to collectively begin to address some of Canada’s most intractable social problems. The AD learning group focused on peer-based learning and application, in an environment that created trust and respect among participants. The AD learning group was successful not only in improving individual and organizational efforts to accelerate and scale impact, but also in catalyzing a field of practice in Canada that focused on generating new social innovations, and scaling up and deepening the impact of those innovative initiatives. More than a decade later, the experience contains valuable lessons about effective scaling strategies, and about how to design applied learning approaches to support social innovators.

Scaling Social Impact: Strategies for Spreading Social Innovations | CASE - Dees, J. Gregory; Battle Anderson, Beth; Wei-Skillern, Jane (2004)
How can social entrepreneurs effectively scale their impact to reach the many people and communities that could benefit from their innovations? As policy expert and author Lisbeth Schorr observed: “We have learned to create the small exceptions that can change the lives of hundreds. But we have not learned how to make the exceptions the rule to change the lives of millions.” If we are serious about tackling social problems on a large scale, we need to develop more effective tools to address this challenge.

The Open Book of Social Innovation - Murray, Robin; Caulier-Grice, Julie; Mulgan, Geoff (Young Foundation, NESTA, 2010)
This book is about the many ways in which people are creating new and more effective answers to the biggest challenges of our times: how to cut our carbon footprint; how to keep people healthy; how to end poverty. It describes the methods and tools for innovation being used across the world and across the different sectors – the public and private sectors, civil society and the household – and in the overlapping fields of the social economy, social entrepreneurship and social enterprise. It draws on inputs from hundreds of organisations around the world to document the many methods currently being used. In other fields, methods for innovation are well-understood. In medicine, science, and business, there are widely accepted ideas, tools and approaches. But despite the richness and vitality of social innovation, there is little comparable in the social field. Most people trying to innovate are aware of only a fraction of the methods they could be using. This book provides a first mapping of these methods and of the conditions that will enable social innovation to flourish.
Keywords: Libre accès; UK